Studi Komparatif terhadap Runtuhnya Eran diLangi’ dalam Kepercayaan Leluhur Toraja dengan Putusnya Hubungan Allah dan Manusia dalam Kejadian 3:1-24 - Henni Tumba’ Sauna; Imelsya Imelsya; Sanhedrin Rio Kassang (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This article aims to see the relationship in the form of similarities between the mythological story of Eran di Langi' in Toraja society and the narrative of the fall of humanity into sin according to Genesis 3, so that these similarities can be a contextual theological contribution for the Toraja Christian community which cannot separate itself from the cultural understanding that has shaped it. his identity. The method used is a qualitative method with a library research approach by collecting various information relevant to the topic or problem that is the object of research with various references from sources that are appropriate to the research topic. The results of this research found that humans' greed and arrogance make them rebel and choose to disobey God, giving birth to sin which makes God angry and breaks the relationship between humans and Himself. The broken relationship between God or Puang Matua and humans is depicted in the mythological story of Eran di Langi' and the fall of humans in Genesis 3. So these two stories are related in the form of similarities.